2008
DOI: 10.1523/jneurosci.2934-07.2008
|View full text |Cite
|
Sign up to set email alerts
|

Parallel Processing of Nociceptive A-δ Inputs in SII and Midcingulate Cortex in Humans

Abstract: The cingulate cortex (CC) as a part of the "medial" pain subsystem is generally assumed to be involved in the affective and/or cognitive dimensions of pain processing, which are viewed as relatively slow processes compared with the sensory-discriminative pain coding by the lateral second somatosensory area (SII)-insular cortex. The present study aimed at characterizing the location and timing of the CC evoked responses during the 1 s period after a painful laser stimulus, by exploring the whole rostrocaudal ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
86
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(99 citation statements)
references
References 73 publications
(78 reference statements)
10
86
0
2
Order By: Relevance
“…Other evidence is provided by the simultaneous pain-evoked activation of these areas which is consistently reported in neurophysiological recordings [Frot et al, 2008;Ohara et al, 2004;Ploner et al, 1999]. The present study complements and extends these observations by showing directly the causal interactions, or better, the lack of causal interactions between these areas and thereby provides further confirmatory evidence for a parallel organization of S1 and S2 in human pain processing.…”
Section: Human Brain Mappingsupporting
confidence: 86%
See 1 more Smart Citation
“…Other evidence is provided by the simultaneous pain-evoked activation of these areas which is consistently reported in neurophysiological recordings [Frot et al, 2008;Ohara et al, 2004;Ploner et al, 1999]. The present study complements and extends these observations by showing directly the causal interactions, or better, the lack of causal interactions between these areas and thereby provides further confirmatory evidence for a parallel organization of S1 and S2 in human pain processing.…”
Section: Human Brain Mappingsupporting
confidence: 86%
“…Traditional electrophysiological approaches inferred possible routes of information flow from the temporal order of activations. The results of these studies showed nearly simultaneous pain-evoked activations in S1, S2 and ACC [Frot et al, 2008;Ohara et al, 2004;Ploner et al, 1999] which differ from more sequential activation patterns in other modalities and suggest a partly parallel organization of pain processing in the human brain. Other studies applied coherence analyses and showed pain-related changes in functional connectivity between brain areas related to pain [Llinas et al, 1999;Ohara et al, 2008;Ohara et al, 2006;Sarnthein and Jeanmonod, 2008].…”
Section: Introductionmentioning
confidence: 73%
“…Moreover, affective disorders such as anxiety and depression frequently occur together with tinnitus (77). Data based on evoked potentials in humans with implanted electrodes in several brain structures indicate that painful stimuli are processed in parallel in the somatosensory cortex and dACC (78), suggesting that the affective and discriminatory aspects are processed simultaneously and not serially.…”
Section: Beyond Sensory Percepts: the Affective Dimensionmentioning
confidence: 99%
“…En accord avec les données de l'imagerie fonctionnelle, les résultats de ces étu-des ont démontré ( Figure 1A, B) : (1) que les patients épileptiques chez lesquels la décharge épileptique est identifiée par l'électrode insulaire (épilepsie insulaire) peuvent avoir, pendant la crise, une sensation douloureuse, et qu'a contrario, il y a très peu d'autres régions cérébrales où les décharges produisent de la douleur [22] ; (2) que sur plus de 4 000 stimulations disséminées dans le cerveau, seules les stimulations sur les électrodes insulaires et dans SII ont entraîné une perception de douleur par le patient. Jusqu'à 13 % des stimulations électriques insulaires et de l'aire SII induisent une sensation douloureuse [23] ; (3) que parmi les électrodes qui enregistrent en continu l'activité électrique cérébrale après une stimulation laser douloureuse, seules les électrodes placées dans l'insula, dans SII et plus rarement dans le gyrus cingulaire antérieur [24], le cortex somato-sensoriel primaire ou le cortex moteur primaire [9] enregistrent des réponses. Ainsi, cette approche confirme l'intérêt essentiel de ces régions dans la réponse à la douleur [25,26].…”
Section: La Physiologie De La Douleur Ou Nociceptionunclassified